PROTOTYPE USER INTERFACE CUTI PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI SUMBAWA BERBASIS LOCAL ARE NETWORK (LAN) - Yuliadi Idrus; M. Julkarnain; Rodianto (Jurnal Informatika Teknologi dan Sains, 2021)
Leave is one of the activities of leaving work for a certain period of time for personal activities. Technological advances have had many positive impacts on agencies and companies in providing services to their employees. The Department of Manpower and Transmigration of Sumbawa Regency is a government agency that has many employees, where leave services are still done manually. To support leave services for employees, a leave service application is needed that makes it easier for employees to apply for leave and makes it easier for the staffing department to manage leave data. This application was built using the prototype method with PHP programming and MySQL database. With this application it provides benefits in conveying information quickly, and makes it easier for employees to be able to apply for employee leave and leave to access information.